Budget impact of intravenous ferric carboxymaltose in patients with chronic heart failure and iron deficiency in France. (25th April 2019) - Bourguignon, Sandrine; Faller, Mathilde; Champs, François‐Olivier; Moutier, Hélène; Levesque, Karine; Caranhac, Gilbert; Cohen‐Solal, Alain
Abstract: Aims: This analysis aims to evaluate the budget impact of intravenous iron therapy with ferric carboxymaltose for patients with systolic chronic heart failure and iron deficiency, from the perspective of the French public health insurance. Methods and results: A budget impact model was adapted to forecast the budget impact over 5 years, according to two scenarios: one where patients receive ferric carboxymaltose according to market share forecast and another where patients are not treated for iron deficiency. Clinical data were extrapolated from pooled data from four randomized controlled trials. The time horizon was extended to 5 years by applying transition probabilities estimated from the CONFIRM‐HF trial. Epidemiological parameters for France were derived from the literature. Cost parameters were derived from national available databases. In the base case analysis, the modelled 5 year cost difference between the scenarios with ferric carboxymaltose vs. no iron deficiency treatment in a population of 189 334 prevalent and incident patients led to €0.8m savings. The cumulative savings resulted from a reduction in the hospitalization costs associated with worsening heart failure (€−35.8m) as well as a reduction in the follow‐up costs (€−2.9m). These cost savings outweighed the costs of ferric carboxymaltose treatment (€37.7m). Sensitivity analyses showed that the budget impact varied from €−34m to €+146m. Parameters with the most impact on the budget were the hospitalization rate for patients not treated for iron deficiency, the number of ambulatory sessions needed, the absence of hospitalization cost differentiation between New York Heart Association classes, and administration settings costs. Conclusions: Iron deficiency treatment with ferric carboxymaltose in systolic chronic heart failure patients results in an improvement of New York Heart Association class and thereby increases the well‐being of the patients, while providing an overall cost saving for the French national health insurance.